Analysis Of The Addition Of Steel Plates Reviewed to The Compresivve Strength Capacity Of The T-Beam - Pangestuti, Endah Kanti; Fitriyandi, Wage Dwi; Ramadhan, Fajar Arya; Azman, Mohamed Nor Azhari (Universitas Negeri Semarang, 2023)
Reinforced concrete is used in various constructions, such as buildings, bridges, dams, road pavement, tunnels, etc. Structural strengthening of reinforced concrete beam can be done in various ways, which one is the addition of steel plates bonded to the compression area. Steel plates with a width of 150 mm and 300 mm with a thickness of 2 mm are expected to increase the compressive strength of reinforced concrete beams. Plate installation uses Sikadur 31 CF-Normal adhesive to attach steel plates and beams, and it is hoped that composite properties will occur on both of them. The test object samples were 5 beams consisting of 1 control beam and 4 reinforcement beams with a quality of 10 MPa. The beam sample has dimensions of 75 mm flange width and 80 mm flange height, 150 mm bottom width, 250 mm h height, 300 mm top width. The flexural strength test was carried out with a loading frame in two-point loading. The results of the study of adding plates showed an increase in beam capacity compared to the control beam. The percentage increase in beam capacity of test objects BP 1(1) and BP 1(2) with 150 mm wide plate reinforcement was 17.19% and 18.85%. The increase in beam capacity of BP 2(1) and BP 2(2) specimens with 300 mm wide plate reinforcement was 26.82% and 28.02% respectively